A one-pot, multicomponent reaction for the synthesis of novel 2-alkyl substituted 4-aminoimidazo[1,2-a][1,3,5]triazines - Lim, Felicia Phei Lin; Tan, Lin Yuing; Tiekink, Edward R. T. *; Dolzhenko, Anton V (Royal Society of Chemistry, 2018)
A highly selective, one-pot, three-component synthesis of novel 2-alkyl-substituted 4-aminoimidazo[1,2-a] [1,3,5]triazines has been developed. The scope of the method was explored in two dimensions, varying the structures of trialkyl orthoesters and 2-aminoimidazoles in their reactions with cyanamide. Conveniently performed under microwave irradiation, this method was also proved to be efficient under conventional heating. A library of 24 novel compounds was prepared in high purity using this multicomponent approach. Molecular and crystal structures of representative molecules were studied using X-ray crystallography.